2008
DOI: 10.5194/angeo-26-2203-2008
|View full text |Cite
|
Sign up to set email alerts
|

Multi-instrument observations of nightside plasma patches under conditions of IMF <I>B<sub>z</sub></I> positive

Abstract: Abstract.Results are presented from two multi-instrument case studies showing patches of cold, long-lived plasma in the winter nightside ionosphere during times when the zcomponent of the Interplanetary Magnetic Field (IMF B z ) was positive. These enhancements were coincident with the antisunward convective plasma drift, flowing from polar to nightside auroral latitudes. In the first case, on 5 December 2005 with IMF B y negative, two regions of enhanced electron density were observed extended in MLT in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
(38 reference statements)
1
5
0
Order By: Relevance
“…It was therefore suggested that the patches associated with IMF B z positive had entered the polar cap during conditions of IMF B z negative. This result was supported by observations of plasma in the nightside ionosphere using the European Incoherent Scatter (EISCAT) Svalbard Radar (ESR), where plasma observed during IMF B z positive was shown to have crossed the solar terminator in the polar region when IMF B z was negative [ Wood et al , 2008]. This study also illustrated cross‐polar transport under IMF B z positive when IMF ∣ B y ∣ ≫ ∣ B z ∣.…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…It was therefore suggested that the patches associated with IMF B z positive had entered the polar cap during conditions of IMF B z negative. This result was supported by observations of plasma in the nightside ionosphere using the European Incoherent Scatter (EISCAT) Svalbard Radar (ESR), where plasma observed during IMF B z positive was shown to have crossed the solar terminator in the polar region when IMF B z was negative [ Wood et al , 2008]. This study also illustrated cross‐polar transport under IMF B z positive when IMF ∣ B y ∣ ≫ ∣ B z ∣.…”
Section: Introductionsupporting
confidence: 74%
“…The modeled and observed values at the final location were compared and agreed within experimental uncertainties. PLASLIFE had also been used previously to assist in the interpretation of observations in the nightside ionosphere [ Pryse et al , 2006; Wood et al , 2008].…”
Section: Instrumentation and Simulationmentioning
confidence: 99%
“…The results of the superposed epoch analysis (Figure ) for IMF Bz follow the reasoning of Sojka et al [] and Coley and Heelis [] that a majority of polar patch detections coincides with a southward IMF. However, the large IMF Bz standard deviation suggests the development of polar patches also during positive IMF Bz conditions which has been shown by Wood et al [] and Hosokawa et al []. The results of the IMF By analysis indicate that IMF By is mainly positive in the SH and negative in the NH.…”
Section: Discussionmentioning
confidence: 58%
“…Traditionally, the polar cap has been thought to be dominated by Sun‐aligned arc structures for positive IMF Bz, and polar cap patches for negative IMF Bz [ Crowley , 1996]. Most reports of polar cap patches are for negative IMF Bz conditions [e.g., Buchau et al , 1983; Rodger et al , 1994a; McEwen and Harris , 1996], but Oksavik et al [2006a] reported a special case where a patch formed inside a northward IMF lobe cell due to an extended period of local particle precipitation poleward of the dayside open/closed boundary (OCB), and Wood et al [2008] observed plasma of dayside origin in the midnight sector during northward IMF.…”
Section: Introductionmentioning
confidence: 99%